Effect of NPK fertilizer dose and GA3 concentration on growth, yield, and yield quality of Coix lacryma-jobi L. var. ma-yuen from ratoons - Nurmala, Tati; Septian, Falih Ijlal; Wahyudin, Agus; Wicaksono, Fiky Yulianto (Kultivasi, 2023)
One type of cereal that can be used as a functional food is hanjeli (Coix lacryma-jobi L.). Hanjeli production has many problems, i.e., low productivity and long life. Hanjeli cultivation from ratoons has several advantages, including reduced production costs, shorter lifespan, and less water requirement. Fertilization of NPK and application of GA3 as gibberellin hormone are expected to increase the growth and yield of hanjeli. This study aims to determine the interaction effect between NPK and GA3 on the growth and yield of hanjeli from ratoon. This experiment was carried out at the Experimental Field of the Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, Sumedang Regency, West Java, from August to December 2020. The experimental design used a Randomized Block Design, while the treatment design consisted of 2 factors. The first factor was the dose of NPK fertilizer which consisted of 3 levels, namely 100, 200, and 300 kg. The second factor was the concentration of GA3, consisted of 3 levels, namely 0, 10 and 20 ppm. All treatments were repeated 3 times. The results showed that there was an interaction effect between NPK fertilizer application and GA3 concentration on growth and yield of hanjeli, namely plant height, number of tillers, number of branches, leaf area index, number of productive tillers, grain weight per plant, harvest index and grain size and hardness. At a high concentration of GA3, increasing NPK fertilizer dose could improve the growth, yield, and yield quality of the hanjeli.